Geotechnical Properties of Waste Soil from Open Dumping Area in Malaysia. - Omar, Husaini; Md Yusoff, Zainuddin; Mohd Pauzi, Nur Irfah (2011)
Waste soil consists of waste material such as concrete debris, decayed wood, plastics and others. The heterogeneous content of waste soil makes the geotechnical properties difficult to categorize and analyzed. Laboratory works such as compaction test, consolidation test, triaxial and direct shear test are conducted on waste soil to know its geotechnical properties. Based on standard proctor test, the waste soil has a maximum dry density of 1567 kg/m3 with optimum moisture content of 29%. The oedometer test shows the maximum displacement of 4 mm within 100 minutes. Based on direct shear test, the undrained cohesion is in the range of 2- 4 kPa and angle of friction of 140-27o. The triaxial test on unconsolidated undrained condition showed that the cohesion is 3 kPa and angle of friction on the range of 00 to 10.50. These geotechnical properties are important to be used for foundation design for future development at open dumping area in Malaysia.